Simultaneous observation of the magnetic and electric behavior in a correlated system near a metal-semiconductor transition: ESR in pellets of conducting polymers - Kondo, J. M. [UNESP]; Walmsley, L. [UNESP]; Rettori, C.; Sercheli, M. S.; Correa, A. A.; Pereira, E. C. (American Physical Society (APS), 2009)
Electron spin resonance (ESR) experiments show, at the metal-semiconductor transition temperature of a conducting polymer, the distinct contributions of the disordered and crystalline regions. In the more disordered regions of the polymer the polarons experience an antiferromagnetic coupling. As the level of disorder decreases, when small crystalline regions appear, there is a tendency, in some temperature range, for the polarons to interact ferromagnetically. For more ordered regions or crystalline regions of larger sizes, there is a competition between localized ferromagnetic coupled polarons and delocalized ones, that is, between localization and delocalization. The possibility to fit the ESR data for one of the samples using two Dysonian lines, one for each phase, allows one to follow the general behavior of the microwave conductivity as a function of the temperature. The semiconducting behavior of the disordered phase is clearly observed, as well as the true metallic behavior of the crystalline phase revealed by the increase in conductivity with the decrease in temperature. © 2009 The American Physical Society.